The urban and territorial planning during the last fifty years in mexico (2007)
The urban and territorial planning in Mexico started late, and always federal, state and local governments haven’t been able to forecast the long term issues, but instead the long seventy years in which the governors were supported by the Partido Revolucionario Institucional (PRI) started urban structures that were never finished by their successors. However, depending on successive Secretaries of State planning programs have been made relying on national and international specialists, but the quantity of the proposed resources exceed the public budget. Lately, the Mexico City Government has announced numerous expropriations in order to finish with the illegal commerce; as well as ending the construction of a new subway line and the new suburban train which will communicate Mexico City with the State of Mexico; also finishing the Periferico’s (elevated transport) second floor.